1994
DOI: 10.1029/93jd02991
|View full text |Cite
|
Sign up to set email alerts
|

Ozone formation at a rural site in the southeastern United States

Abstract: Trace gas measurements pertinent to understanding the transport and photochemical formation of 03 were made at a surface site in rural Georgia as part of the Southern Oxidant Study during the summer of 1991. It was found that there was a strong correlation between 03 and the oxidation products of NOx: O3(ppb) = 27 + 2 11.4 (NOy(ppb) -NOx(ppb)), r = 0.78. This fit is similar to that observed at other rural sites in eastern North America and indicates a nominal background 03 level of 27 ppb; values higher than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(130 citation statements)
references
References 31 publications
12
115
1
2
Order By: Relevance
“…The minimum detection limit of the analyzer is about 1 ppbv and its response is about 10 s. Lal et al (1998Lal et al ( , 2000 and Nair et al (2002) have also been employed the same O 3 analyzer described above in their study. The absolute accuracy of these types of system is reported to be 5% (Kleinman et al 1994). …”
Section: Experimental Techniquementioning
confidence: 99%
“…The minimum detection limit of the analyzer is about 1 ppbv and its response is about 10 s. Lal et al (1998Lal et al ( , 2000 and Nair et al (2002) have also been employed the same O 3 analyzer described above in their study. The absolute accuracy of these types of system is reported to be 5% (Kleinman et al 1994). …”
Section: Experimental Techniquementioning
confidence: 99%
“…The OPE x can be derived from the regression slopes of correlations between O x and NO z [Kleinman et al, 1994;Trainer et al, 1993]. Therefore, the accuracy of NO 2 measurement plays an important role in the calculation of OPE x by influencing the quantification of O x and NO z .…”
Section: Ozone Production Efficiency (Ope X )mentioning
confidence: 99%
“…Since the oxidants of NO x can be removed from the O 3 -productionreaction system, Liu et al [1987] defined the number of molecules of O 3 formed per NO x as O 3 production efficiency of NO x (OPE x ), which has been used as an important indicator in studying O 3 chemistry. Trainer et al [1993] and Kleinman et al [1994] found better correlations between O 3 and the oxidation products of NO x , i.e., NO z (= NO y À NO x ) than the sum of reactive nitrogen species, NO y , in the photochemically aged air, based on which the OPE x was revised as Δ[O 3 + NO 2 ] / Δ[NO z ]. Therefore, accurate measurements of NO y and NO x are of importance to understand the formation mechanism of O 3 production, and hence to make the corresponding control strategies for mitigation of photochemical smog.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are only a few days of observations in June, when the campaign ended. The daytime increment in surface ozone is a typical feature of polluted sites and can be associated with daytime photochemical production of ozone from its precursors in the presence of sunlight (e.g Kleinman et al, 1994) and/or through mixing of ozone rich air aloft. 15 The very low levels of ozone (during winter months) were observed during night-time which can be attributed to titration of O3 by NO.…”
Section: Variations In Ozone At Bodementioning
confidence: 99%